Movement and Activity Patterns of Non-Native Wels Catfish (Silurus glanis Linnaeus, 1758) at the Confluence of a Large River and Its Colder Tributary - Daniel Nyqvist; Olle Calles; Gilberto Forneris; Claudio Comoglio (Fishes, 2022)
The establishment and proliferation of non-native fish species can have a range of effects within the local ecosystem, including alteration of food webs, nutrient cycling, pathogen dynamics and predation, sometimes also resulting in changed behavior and distribution of native fish species. Knowledge about movements and activity patterns is important to understand the dynamics of non-native animals in their new environment. The Wels catfish (Silurus glanis Linnaeus, 1758) is considered an invasive species in many places in Western Europe, and regional control programs are in place. Here, using radiotelemetry, we study the movements and activity patterns of invasive Wels catfish at an invasion front within the Po River (Italy); namely, at the confluence between the main river, where the species is abundant, and a colder tributary, the Dora Baltea River, where it is absent. In addition, we also investigate potential spatiotemporal overlap between Wels catfish and native and endangered marble trout (Salmo marmoratus Cuvier, 1829) in the area. A total of nine Wels catfish and eight marble trout were tagged. The Wels catfish showed a very high degree of residency within the study area in the Po River, close to the mouth the colder tributary. Despite this, only one catfish entered the lower reaches of the tributary and did so only occasionally during August. No catfish moved further upstream in the tributary. It is likely that lower temperatures in combination with more challenging hydrodynamic conditions made the tributary unattractive to the catfish. The catfish were active during all times of the day but substantially more so during evenings and at nights. Some, but not all, tagged catfish moved to areas in the main stem upstream of the confluence with the tributary. A large proportion of the tagged marble trout made occasional or longer visits to the Po River, with several individuals becoming resident, but without apparent mortality, in the tagged catfish home range. The high residency of the Wels catfish suggests that removal efforts may do well to initially focus on areas close to the habitats of species under conservation concern.